Aesthetic discourse in environmental poster designs (Al-Academy, 2025)
The current research examines "aesthetic discourse in environmental poster designs" as facts and behaviors that pervade all aspects of life in society. This has been reflected in cultural and social life, characterizing it as discourse. Aesthetic discourse was a fundamental and artistic detail, including its subject matter, the discourse, through stylistic and technical treatments that brought about a transformation unparalleled in previous artistic experiments.Thus, the research problem arose to question the motivations for discourse and the ways in which it manifests itself through artistic treatments, as well as the extent to which aesthetic discourse engages with the system of intellectual and psychological relationships.The first chapter included the research objective and limits, which sought to identify aesthetic discourse in environmental poster designs and define terminology.The second chapter then included the first section and the second section, the theoretical framework. The third chapter addressed the research procedures, represented by the research community and its samples, which amounted to (2) models, the nature of constructing the instrument in its initial and final forms, and the use of appropriate technical means to extract the validity and reliability of the instrument, followed by an analysis of the research sample. The fourth chapter included the research results and conclusions, followed by recommendations and proposals